2006
DOI: 10.1073/pnas.0600592103
|View full text |Cite
|
Sign up to set email alerts
|

Surprising contribution to aminoacylation and translation of non-Watson–Crick pairs in tRNA

Abstract: Molecules of transfer RNA (tRNA) typically contain four stems composed of Watson-Crick (W-C) base pairs and infrequent mispairs such as G-U and A-C. The latter mispairs are fundamental units of RNA secondary structure found in nearly every class of RNA and are nearly isomorphic to W-C pairs. Therefore, they often substitute for G-C or A-U base pairs. The mispairs also have unique chemical, structural, and dynamic conformational properties, which can only be partially mimicked by W-C base pairs. Here, I charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Some chimeras (data not shown) allowed efficient suppression in the absence of Cyc, suggesting that the resulting tRNAs were charged by endogenous E. coli tRNA synthetases. Edman degradation (data not shown) of a reporter protein based on the E. coli dihydrofolate reductase (DHFR) system containing a UAG codon in position 3 (18) revealed the presence of glutamine (80%), threonine (12%), and In vivo binding of tRNA Pyl to PylRS was determined by the yeast three-hybrid method as described in Materials and Methods. L represents loss of aminoacylation efficiency and is calculated as (k cat/KM mutant)/(kcat/KM wild type).…”
Section: Effect Of Mutations In Trna Pyl On In Vitro Charging By and mentioning
confidence: 99%
“…Some chimeras (data not shown) allowed efficient suppression in the absence of Cyc, suggesting that the resulting tRNAs were charged by endogenous E. coli tRNA synthetases. Edman degradation (data not shown) of a reporter protein based on the E. coli dihydrofolate reductase (DHFR) system containing a UAG codon in position 3 (18) revealed the presence of glutamine (80%), threonine (12%), and In vivo binding of tRNA Pyl to PylRS was determined by the yeast three-hybrid method as described in Materials and Methods. L represents loss of aminoacylation efficiency and is calculated as (k cat/KM mutant)/(kcat/KM wild type).…”
Section: Effect Of Mutations In Trna Pyl On In Vitro Charging By and mentioning
confidence: 99%
“…Stop codons also have a similar phenomena, with TAA, TAG and single nucleotide T common while AGG and AGA are rarely used (Cao, Wu and Yan, 2006). As previously reported (McClain, 2006), the start codons for the NAD4L gene and ATP6 gene in Os. tetraspis are TTG and ACA, both of them being unconventional.…”
Section: Genomes and Gene Featuresmentioning
confidence: 79%
“…Similarly, the putative tRNA Arg in Pa. trigonatus contains two non-Watson-Crick base pairs (both A/C) and one mismatch (A/A), appearing to be a new interesting example of mis-and unpaired bp (Roos, Aggarwal and Janke, 2007). It has been shown that non-Watson-Crick G/U and A/C pairings may play an important role in aminoacetylation and translation, primarily because of the conformational flexibility they provided, and unpaired nucleotides in stem regions may yield additional flexibility of the tRNA structure (McClain, 2006).…”
Section: Genomes and Gene Featuresmentioning
confidence: 98%
“…Base pair 49-65 that has been shown to directly influence the translation (McClain 2006) is the only locus outside the anticodon domain (ACD) where the presence of covariations was found in all three domains of life (Fig. 6A,B).…”
Section: T Stemmentioning
confidence: 99%